Expert witnessing in forensic accounting : a handbook for lawyers and accountants - Telpner, Zeph.; Mostek, Michael S. (Boca Raton, Fla. : CRC Press, 2003)
Shows how to be successful in the courtroom through the hands-on experiences of both a certified public accountant and a trial attorney. This book guides readers through the entire judicial process, presenting guidelines from choosing an accountant to analyzing the opposing expert's deposition.
Includes index.
oif 30/03/15
Loan
Keywords: Forensic accounting; Evidence, Expert; united states